2010
DOI: 10.1021/jm100966t
|View full text |Cite
|
Sign up to set email alerts
|

Gd-Complexes of 1,4,7,10-Tetraazacyclododecane-N,N′,N′′,N′′′-1,4,7,10-tetraacetic Acid (DOTA) Conjugates of Tranexamates as a New Class of Blood-Pool Magnetic Resonance Imaging Contrast Agents

Abstract: Gd-complexes of the type [Gd(L)(H(2)O)]·xH(2)O (5a-c), where L is DOTA conjugates of tranexamic acid (4a) and tranexamic esters (4b,c), have been prepared as a new class of MRI blood-pool contrast agents (BPCAs). Thermodynamic stability (K(GdL)) and pharmacokinetic inertness of 5 compare well with or better than those of analogous MRI contrasting agents (CAs) such as Gd-DOTA and Gd-DTPA-BMA. Their R(1)-relaxivities are significantly higher than those of any of the clinically used MRI CAs. T(1)-weighted MR imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 47 publications
4
7
0
Order By: Relevance
“…The kinetic inertness of Gd-DOTA-Am4, Gd-DTPA and Gd-DOTA was assessed via a transmetallation assay using equimolar concentrations of the Gd complexes and ZnCl 2 , in fetal bovine serum. Consistent with previous reports (17)(18)(19)(20), the relaxation ratio R1(t)/R1(0) rapidly increased for samples containing Gd-DTPA, indicative of transmetallation ( Fig. 3A) (21,22).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The kinetic inertness of Gd-DOTA-Am4, Gd-DTPA and Gd-DOTA was assessed via a transmetallation assay using equimolar concentrations of the Gd complexes and ZnCl 2 , in fetal bovine serum. Consistent with previous reports (17)(18)(19)(20), the relaxation ratio R1(t)/R1(0) rapidly increased for samples containing Gd-DTPA, indicative of transmetallation ( Fig. 3A) (21,22).…”
Section: Resultssupporting
confidence: 92%
“…Consistent with previous reports (1720), the relaxation ratio R1(t)/R1(0) rapidly increased for samples containing Gd-DTPA, indicative of transmetallation (Figure 3A). (21, 22) It should be noted that components of fetal bovine serum (e.g.…”
Section: Resultssupporting
confidence: 92%
“…This indicated that the bisamide complex DTDTPA:Gd showed more extensive transmetallation than the parent compound. This behavior was consistent with what was already determined in GdDTPA bisamide series . The reason for this lies in the substitution of two carboxylate groups by two amide groups in the first coordination sphere of Gd 3+ .…”
Section: Resultssupporting
confidence: 92%
“…In a similar approach, Gd-complexes consisting of DOTA conjugates of tranexamic acid and tranexamic esters were prepared as a new class of MRI-BPCAs. The r 1 -relaxivity was significantly higher than those of any of the clinically used MRI CAs [ 161 ]. Table 3 briefly summarizes r 1 , particle size, biotoxicity, specific properties and modality of Gd-CAs.…”
Section: Functionalization Of Gd-npsmentioning
confidence: 99%